City Form and Cognitive Model (diségno, 2024)
In 1975, Rosario La Duca published Cartografia generale della città di Palermo e antiche carte della Sicilia (General cartography of the city of Palermo and ancient maps of Sicily), containing 40 plates and about 100 charts. Among the plates is the Pianta geometrica secondo lo stato presente della città di Palermo capitale del Regno di Sicilia col suo porto, sobborghi, molo e campagna, drawn in 1822 by F. G. C. B. De Behrend.After a brief note on the model, the contribution presents a recent didactic experience related to surveying and digital representation, in which it was decided to study and investigate the De Behrend cartography according to a procedure that, starting from the redrawing of a historical map, arrives at the construction of a physical model of the structure of the 19th century city, in an optical/tactile dimension. The model is to be understood in its double value of outcome and incipit for other studies; if on the one hand it returns an image of the city in its entirety, the result of progressive stratifications, on the other hand it offers the possibility of investigating the morphological aspects of the urban fabric to trigger classificatory processes that never neglect the contribution of History.The construction of the physical model allows the transition from the abstraction of the two-dimensional representation of the iconographic document to the material concretisation of the building structure of the historic city. Sensory involvement as an amplifier of knowledge finds its concrete dimension in the ‘model’.
Keywords: reading; interpretation; survey; redesign; model